2017
DOI: 10.1002/biof.1354
|View full text |Cite
|
Sign up to set email alerts
|

Hydrogen sulfide attenuates homocysteine‐induced cognitive deficits and neurochemical alterations by improving endogenous hydrogen sulfide levels

Abstract: Hyperomocysteinemia (HHcy) has been associated with mild cognitive impairment and dementia. Hydrogen sulfide (H S) has been suggested to be an endogenous modulator of neuronal functions. However, the effect and mechanisms involved in beneficial effect of H S has not been investigated in homocysteine (Hcy)-induced cognitive deficits. This study has been designed to evaluate the effect of exogenous H S on behavioral deficits and neurochemical alterations in HHcy animals. Hcy levels were significantly elevated in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
13
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 36 publications
(19 citation statements)
references
References 86 publications
5
13
1
Order By: Relevance
“…*p < 0.05, significantly different from control group; # p < 0.05, significantly different from Hcy group. Hcy: homocysteine; H 2 S: hydrogen sulfide; NaHS: sodium hydrosulfide hydrate found out that Hcy mice have low production of endogenous H 2 S than that of control, which fits the earlier report suggesting that decrease in the endogenous level of H 2 S results from Hcy-induced BBB permeability (Kumar et al, 2017;Tyagi et al, 2010). H 2 S is a vasorelaxant and at physiological concentrations dilated the arterioles via the opening of adenosine triphosphate sensitive K + channels .…”
Section: Discussionsupporting
confidence: 84%
See 1 more Smart Citation
“…*p < 0.05, significantly different from control group; # p < 0.05, significantly different from Hcy group. Hcy: homocysteine; H 2 S: hydrogen sulfide; NaHS: sodium hydrosulfide hydrate found out that Hcy mice have low production of endogenous H 2 S than that of control, which fits the earlier report suggesting that decrease in the endogenous level of H 2 S results from Hcy-induced BBB permeability (Kumar et al, 2017;Tyagi et al, 2010). H 2 S is a vasorelaxant and at physiological concentrations dilated the arterioles via the opening of adenosine triphosphate sensitive K + channels .…”
Section: Discussionsupporting
confidence: 84%
“…Chan and Wong (2017) recently reported that there is no definitive answer to this question at present. Several in vitro and in vivo studies have recently shown that the H 2 S protective effect is dose dependent (Kumar et al, 2017;Z. Li, Wang, Xie, Yang, & Zhang, 2011;Wang et al, 2014;Yan et al, 2006).…”
Section: Introductionmentioning
confidence: 99%
“…Increased anxiety may result from decreased S-adenosylmethionine-dependent synthesis of catecholamines due to an excess of homocysteine [ 25 ]. Indeed, reduced biosynthesis of dopamine, serotonin, and noradrenalin along with increased activity of the monoamine oxidases–MAO-A and MAO-B in the cerebral cortex and hippocampus was shown in rats with prenatal and postnatal hHcy [ 60 , 61 ].…”
Section: Discussionmentioning
confidence: 99%
“…Several studies revealed cellular mechanisms of neuroprotective effects of H 2 S in homocysteine induced neurotoxicity in a postnatal model of hHcy [ 35 , 36 , 57 ] which are also applicable to our model of hHcy. H 2 S prevented the increased anxiety of hHcy rats due to elevation of the catecholamines level [ 61 ]. In chronic unpredictable mild stress, H 2 S protected hippocampal damage through activation of the BDNF-TrkB (brain-derived neurotrophic factor—tyrosine protein kinase B) pathway and inhibition of hippocampal CA1 long-term depression due to inhibition of the JNK signaling pathway [ 95 , 101 , 102 ].…”
Section: Discussionmentioning
confidence: 99%
“…In our present study, we demonstrated both the decreased expression of H 2 S-synthesizing enzyme (CBS and 3-MT) and the inhibition of H 2 S generation in the hippocampus of SD-exposed rats. Studies showed that the decreased activity of CBS mediates homocysteine- and formaldehyde-induced cognitive deficits (Tang X. Q. et al, 2013; Kumar et al, 2017). Likewise, the level of endogenous H 2 S is decrease in the animal model and the patients of Alzhermer’s disease (Liu et al, 2008; Liu H. et al, 2015; Karimi et al, 2017).…”
Section: Discussionmentioning
confidence: 99%